A one-dimensional solid-state NMR approach for 14NH/14NH overtone correlation through 1H/1H mixing under fast MAS. Issue 40 (5th October 2018) - Pandey, Manoj Kumar; Nishiyama, Yusuke
Abstract : A proton-detected one-dimensional 14 N OT / 14 N OT / 1 H correlation NMR method to achieve NH/NH proximities in naturally abundant samples. Abstract : Homonuclear correlations are key to structural studies using solid-state NMR. In this contribution, using 14 N overtone transition (OT) as a selective excitation approach, we propose a proton-detected one-dimensional (1D) 14 N OT / 14 N OT / 1 H correlation solid-state NMR method mediated through 1 H/ 1 H mixing at fast magic angle spinning to achieve NH/NH proximities in naturally abundant samples. The proposed method is time efficient by a factor of ∼7.5 in comparison to the existing fundamental 14 N frequency-based three-dimensional (3D) 14 N/ 14 N/ 1 H correlation method.